2022
DOI: 10.3390/v14122645
|View full text |Cite
|
Sign up to set email alerts
|

Viral Coinfections

Abstract: In nature, viral coinfection is as widespread as viral infection alone. Viral coinfections often cause altered viral pathogenicity, disrupted host defense, and mixed-up clinical symptoms, all of which result in more difficult diagnosis and treatment of a disease. There are three major virus–virus interactions in coinfection cases: viral interference, viral synergy, and viral noninterference. We analyzed virus–virus interactions in both aspects of viruses and hosts and elucidated their possible mechanisms. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 215 publications
(223 reference statements)
0
5
0
Order By: Relevance
“…Viral co-infections are common in nature. However, studies and available data on viral co-infections in fish aquaculture are limited [42,43]. In recent years, infectious events of fish papillomavirus co-infected with other viruses were found in fish aquaculture, such as SaPV1 co-infected with iridovirus and polyomavirus [23], SgPV1 co-infected with herpesvirus [24].…”
Section: Discussionmentioning
confidence: 99%
“…Viral co-infections are common in nature. However, studies and available data on viral co-infections in fish aquaculture are limited [42,43]. In recent years, infectious events of fish papillomavirus co-infected with other viruses were found in fish aquaculture, such as SaPV1 co-infected with iridovirus and polyomavirus [23], SgPV1 co-infected with herpesvirus [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, CsPaV and CsPV were isolated and analyzed simultaneously from the diseased Chinese tongue sole, and the FISH results revealed that the transcripts of the two viruses could be detected in single cells of the infected tissues, hinting that the emerging viral disease was caused by a co-infection of the two viruses. Viral co-infections are common in nature [37,38]. However, studies and available data on viral co-infections in fish aquaculture are limited.…”
Section: Discussionmentioning
confidence: 99%
“…All of them can establish latent infections in specific tissues, which are different for each virus'’ [ 17 ]. Coinfection can be marked as simultaneous or successive infection of a single cell or host by multiple pathogens [ 18 ] Traylen et al., illustrated reactivation of virus as the process by which a latent virus switches to a lytic phase of replication [ 19 ]. Data from laboratory diagnosis of COVID-19 and Herpes virus were included irrespective of gender, age and geographical distribution.…”
Section: Methodsmentioning
confidence: 99%